UDH Inc. : Automatic Mini Dishwashing Machine / Ahmad As-Syaffi Ahmad Misbah ...[et al.] - Ahmad Misbah, Ahmad As-Syaffi; Md Nor, Muhammad Syazwan; Shahrol Ismail, Zainul Zikry; Hosni, Nurul Balqis (2019)
Our mission is to innovate product ass that reduce a significance amount of cost and energy. Our company guarantees that our product is an eco-friendly product as our vision is not only to provide technology to people but also creating technology that could conserve energy. In order to ensure the business will experience sustainable growth, UOH Inc. plans to develop its new product which is an automatic dishwasher machine.